Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T15:50:43+01:00
D)
-(2x-1)=4
-2x+1=4 | -1
-2x=3 | :(-2)
x=(-1½)

e)
2(x+1)=x
2x+2=x |-x
x+2=0 |-2
x=(-2)

f)
2t-(3t+1)=6
2t-3t-1=6
-t-1=6 |+1
-t=7 |: (-1)
t=(-7)

g)
-(4+x)=2(3-x)
-4-x=6-2x |+2x
-4+x=6 |+4
x=10

h)
3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y+18=2y+18
jest to równanie tożsamościowe

i)
(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3 |+17
-5x=20 |:(-5)
x=(-4)

2 3 2
2010-03-17T15:52:03+01:00
D) -2x+1=4
-2x=4-1
-2x=3
x= - 3/2

e) 2x+2=x
2x-x=-2
x=-2

f) 2t-3t-1=6
2t-3t=6+1
-t=7
t=-7

g) -4-x=6-2x
-x+2x=6+4
x=10

h) 3y+18-y= 2y+18
3y-2y=18-18
y=0

i) x-7-6x-10=3
x-6x=3+10+7
-5x=20 / (-5)
x= -4
1 1 1
2010-03-17T15:56:02+01:00
D) -(2x-1)=4
-2x+1=4/-1
-2x=3/:(-2)
x=1,5

e) 2(x+1)=x
2x+2=x/-x
2x-x+2=0/-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6/+1
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x/+4
-x=6-2x+4/+2x
2x-x=6+4
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18/-2y
3y-2y-y+18=18/-18
0=18-18
0=0
równanie tożsamościowe

i) (x-7)-2(3x+5)=3
x-7-6x-10=3/+10
x-7-6x=13/+7
x-6x=20
-6x+x=20
-5x=20/:(-5)
x=-4
3 3 3